Design of Centralized PI Controllers by Synthesis Method for TITO Systems. Issue 4 (2nd October 2017) - Besta, Chandra Shekar; Chidambaram, Manickam
Abstract: In this paper, the simple method of designing decentralized Proportional–Integral-Derivative (PID) controllers by the synthesis method is extended to design centralized PID controllers. The centralized controllers give improved responses and reduced interactions when applied to systems with λij  < 1. The effectiveness of the proposed method is compared with that of the available decentralized and separately with the centralized controllers. The robustness of these controllers is evaluated by the inverse maximum singular value versus frequency plot for both the input uncertainty and the output multiplicative uncertainty. Simulation results for two 2 × 2 systems demonstrate that the proposed method guarantees robust stability and provides best servo and regulatory responses.